Issues on land acquisition in Kg Baru Kuala Lumpur from property owners’ perspectives - Tajul Ariffin, Izyana (2024)
This research study the issues on land acquisition in Kampung Baru Kuala Lumpur from property owners’ perspectives. Land acquisition is crucial for enhancing the image and economic of the country by redeveloped the potential location from undeveloped to strategical place for residential, commercial, and industrial based on the land use to generate maximum profits and increase the economy levels. However, the limitation and scarcity of land makes the particular area is hard to be developed. This can be overcome by having government intervention on acquiring the land. In the context of land acquisition of Kampung Baru, majority of the property owners accepted the land acquisition as in return they would be given replacement units in the new high-rise development project when it is completed (FMT Reporters, 2023). Meanwhile, 33% of the property owners are refused and objected it. This makes the redevelopment project delayed as some of them refuse to give up their lands. To address this issue, this research aims to explore and identify the problem of delayed of land acquisition in Kampung Baru with the proper and in-depth observation towards the affected property owners regarding their dissatisfaction, experience, and factors of objecting on the compulsory land acquisition in Kg Baru, Kuala Lumpur. From literature, several issues of land acquisition like inadequate compensation, delays in developing the area, delays in giving the awards and compensation, and miscommunication and improper explanation from the authorities. This study took place in Kg Baru, Kuala Lumpur as it is the central capital of Malaysia and known for its limited land resource and high profitability for mega redevelopment projects as it is the most strategic location with many facilities and amenities that good for investment and economic growth. Through qualitative research methods, including interviews with affected property owners in Kg Baru, this study identifies issues relating to the overall land acquisition practice.